EXPLORING STUDENTS’ PERCEPTION ON THE USE OF MY BEST MOODLE IN LEARNING ENGLISH DURING COVID-19 OUTBREAK: - - mike amelia; Fitri Handayani (Journal of English Language Learning, 2022)
This article describes a design research project at Bina Sarana Informatika University to construct an e-learning web-based moddle. During the Covid-19 outbreak, the study used My Best Moddle of instructional growth in learning process. This article focuses on how students' perceptions of the moodle's implementation were evaluated. The methode of research is descriptive quantitiave. The study included a number of fourth-semester students of Bina Sarana Informatika University as a population and 30 students were selected by using random sampling technique. A questionnaire and an interview were used to gather information. The students thought the My Best e-learning moodle was helpful in enhancing their motivation to learn English as well as their relationships with each other and the lecturer during online learning. Students also agreed that the My Best e-learning module was simple to utilize. It can be stated that the students’ perception on the use of My Best in learning English have positive respond. The students' issues were a drop in seriousness and degree of concentration during online studying. It is influenced by the learning environment. The internet connection is unstable, and devices like smartphones and laptops are not equipped to facilitate accessing e-learning. Materials were also challenging for the students to understand, and they had trouble completing their own tasks as well as group projects that required internet collaboration. The final issue was how easily stressed out students became while engaging in online learning. Based on the findings, it can be said that while students benefited from e-learning, there are some issues with its abrupt adoption and lack of planning. So that the objectives and standards of education can be achieved.